Nesbitt Type Inequalities - Wei-Kai Lai (International Journal of Mathematics And its Applications, 2018)
In 2009 Wei and Wu introduced an n-variable version of Nesbitt's inequality. In this paper we provide a different proof using Radon's inequality. We also use the same technique to prove several of its variations.